ROLE OF REVERSE SURAL ARTERY FLAP FOR SOFT TISSUE DEFECTS OF LOWER LIMB: EXPERIENCE WITH 66 CASES - Cheema, Saeed Ashraf; Malik, Adnan Latif; Asim, Muhammad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Reverse sural artery flap has proved to be a good option to reconstruct soft tissue defects of lower limb and foot region. Different studies, however, speak of its use in different areas depending upon the individual experiences. Various modifications of the flap technique have been described in various studies. This study highlights many of the modifications in a single series and the fact that extending its arc of rotation, flap has capacity to deal with defects of middle and lower thirds of leg, heel, ankle, sole, dorsum and forefoot. Methods: In this case series, flap was utilized in 66 cases. Extension of skin paddle up to knee joint crease level increased the arc of rotation and as a result series witnessed this flap covering defects at the forefoot level. A good number of modifications suggested in literature were utilized to get optimal results. Results: Lower leg defects were covered in 26 cases. Heel was the site of defect in 18 patients. Dorsum foot needed soft tissue cover in other 15cases. Flap was successful in 62 cases and it failed in 4 cases. Conclusions: Flap due to its long arc of rotation has the capacity to deal the defects of middle and lower thirds of leg, heel, ankle, sole, dorsum and forefoot. Various modifications can be wisely utilized to increase the efficacy of the flap. Keywords: Flaps, Lower limb Reconstruction, Perforator flaps, Reverse Sural Artery Flap